2014
DOI: 10.5539/gjhs.v7n4p12
|View full text |Cite
|
Sign up to set email alerts
|

Emolabeling Effectively Reduces the Influence of Ambiguous Labeling on Food Packages Among Grocery Store Shoppers

Abstract: Despite increased regulations and policy enforcement for nutrition labeling, ambiguous labels on food items can still have deleterious effects on consumer perceptions of health. The present study used a counterbalanced within-subjects design to test if emolabeling—the use of emoticons to convey health information (happy = healthy; sad = not healthy)—will reduce the effects of ambiguous labels on consumer perceptions of the healthfulness of a food item. 85 grocery store shoppers were shown nutrition labels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A number of studies indicate that consumer understanding can be improved by the use of simple and user-friendly label formats such as Traffic Lights system (Borgmeier and Westenhoefer, 2009;Kelly et al, 2009;Scarborough et al, 2015). Apart from Traffic Light system, consumers are comfortable with "Nutrition Byte" labelling (Driskell et al, 2009) and emolabelling (Privitera et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicate that consumer understanding can be improved by the use of simple and user-friendly label formats such as Traffic Lights system (Borgmeier and Westenhoefer, 2009;Kelly et al, 2009;Scarborough et al, 2015). Apart from Traffic Light system, consumers are comfortable with "Nutrition Byte" labelling (Driskell et al, 2009) and emolabelling (Privitera et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…strategy in which emotional correlates of health are conveyed using simple emoticons (happy = healthy; sad = not healthy) that are universally recognized even at pre-to early-literacy ages (Darwin, 1979;Privitera et al, 2013). Evidence indicates that this labeling strategy can improve knowledge about the healthfulness of foods among children (Privitera et al, 2013) and adults (Privitera, Brown, & Gillespie, 2015). A more recent study showed that adding emolabels onto plain food containers could further promote healthy food choices among 5 to 11 year old children (Privitera, Phillips, Misenheimer, & Paque, 2014).…”
Section: Introductionmentioning
confidence: 96%